Pengaruh Content Marketing dan Online Costumer Review pada TikTok Shop Terhadap Keputusan Pembelian Produk MS Glow : Studi pada Mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar - Syamsidar Syamsidar; Andi Mustika Amin; Ichwan Musa; Siti Hasbiah; Nurul Fadilah Aswar (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of content marketing and online customer reviews on TikTok Shop on purchasing decisions for MS Glow products. This research is quantitative research with a descriptive approach. The sample used was 100 students of the Management Study Program, Faculty of Economics and Business, Makassar State University. Data collection was carried out using observation, literature study, and survey methods using a questionnaire. The method of data analysis uses Multiple Linear Regression Analysis using two statistical test methods, namely the t test (partial test) and the f test (simultaneous test) using Statistical Product and service Solution (SPSS). Based on the research results, the results of the F test hypothesis show the value of F count (74.023) > F table (3.09) with a significance level of 0.001 < 0.05, which means that the independent variables (content marketing X1, and online costumer review X2) simultaneously (together) have a positive and significant influence on purchasing decisions (Y). Meanwhile, the t test results obtained the t value on the Content Marketing variable (3.232) > t table (1.660) with a significance level of 0.002 < 0.05, which means that the Content Marketing variable (variable X1) partially has a positive and significant effect on purchasing decisions (variable Y). The Online Customer Review variable has a t value (4.701) > t table (1.660), with a significance level of 0.001 < 0.05, which means that the Online Customer Review variable (variable X2) partially has a positive and significant effect on purchasing decisions (variable Y).